THE ROLE AND SIGNIFICANCE OF FINE ART IN PREPARING FUTURE FINE ART TEACHERS FOR INDEPENDENT OR CREATIVE ACTIVITY - Nusharov Bobur Bolbekovich (Scholar Express Journal, 2023)
The process of depicting objects in fine art relies primarily on visual intuition and perception as an expression of real existence. The sense of sight is born as a result of the impact of electromagnetic waves on the light receptors of our eyes. A person learns the laws of nature and objects and many of their unique features only through the sense of sight. Among them, the illumination of the world of objects occupies an important place, which serves the viewer to make the world alive and colorful, that is, it gives the opportunity to feel and perceive. In the process of working from nature, students learn the laws of the location of objects in space and their perception through visual analyzers. The formation of practical skills is closely related to the acquisition of the laws of perception of nature and theoretical knowledge of depicting the depicted object on a flat surface. The process of teaching drawing is in a certain sense related to the education and development of vision in future artists, to know all the properties of these objects in connection with each other, which is based on constant observation and color relationships
Keywords: art; fine art; object; colour